Development of an AHP hierarchy for managing omnichannel capabilities: a design science research approach - Jochen Wulf (Business Research, 2020)
Because of the importance of omnichannel services in today's consumer markets, B2C organizations have a high demand for management instruments that support the organizational development of omnichannel capabilities. Prior literature acknowledges that the shift to omnichannel paradigm demands not only technological modifications but also an organizational transformation. However, it remains unclear which capabilities an organization requires and how they can be developed. We address this research gap and construct an analytic hierarchy process (AHP) hierarchy by applying design science research methodology. The developed AHP hierarchy supports capability management in the knowledge acquisition phase. The availability of this hierarchy further is a precondition for implementing an AHP method that supports the selection and steering of projects for omnichannel capability development or the comparison of organizations' capability maturities. We conduct a hierarchy construction procedure that includes various qualitative research methods (focus group, cross-interview analysis, multiple case studies). We demonstrate and evaluate the AHP hierarchy at a global automobile manufacturer, which involved in-depth interviews and a workshop with six executive managers. With our results, we contribute to research on omnichannel management by introducing an instrument that supports omnichannel capability management in B2C organizations during the knowledge acquisition phase.
Keywords: 650; Omnichannel management; Organizational capabilities; Capability model; Analytical hierarchy process; AHP hierarchy; Design science research